COGNITIVE APPROACHES TO IMPROVING LISTENING COMPREHENSION IN LANGUAGE LEARNE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores cognitive listening strategies for language learners, emphasizing techniques that enhance comprehension and listening skills. It introducesstrategies such as predicting content, chunking information, identifying key words, inferring meaning from context, and making connections to prior knowledge. The articlealso highlights the importance of active listening, repetition, and self-reflection inimproving listening abilities. By integrating these strategies, learners can more effectivelyprocess spoken language, overcome challenges, and increase their confidence inunderstanding both everyday conversations and academic content. Overall, the articleserves as a practical guide for language learners looking to sharpen their listening skillsthrough cognitive approaches.